Organizational moral harassment: Attack on the dignity of the worker? - Melo, Rebeca Magalhães (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
Human rights are based on the principle that everyone is born free and equal with respect to dignity and their rights. The Universal Declaration of Human Rights, based on this principle, classifies civil and political rights, and social and economic rights. Human dignity presupposes guarantee of rights, especially with regard to respect for social security, standard of living and effective adaptation to health and work. This study aims to analyze the fundamental right to work with a focus on organizational moral harassment and the guarantee of the right to dignity at work. Questions: What is organizational bullying in the context of banking work? How is organizational bullying seen at work legally? What guarantees does the worker have in relation to protection from harassment at work? How does the legislation deal with this issue? Note that rights are completed / interrelated and are aimed at maintaining human dignity, needing to be well defined in a legal way or consisting of bullying, what are its consequences and how they can be avoided. Moral harassment is considered an unacceptable practice in the workplace, and should be prevented by programs of compliance in public and private companies, which promotes a set of processes aimed at the development of legal instruments that involve policies of use and involvement of the I harass at and at work, thus preserving the integrity and dignity of the people who work at the company.